Sexual injustice : Supreme Court decisions from Griswold to Roe - Stein, Marc (The University of North Carolina Press, 2010)
The U.S. Supreme Court of the 1960s and 1970s is typically celebrated by liberals and condemned by conservatives for its rulings on abortion, birth control, and other sexual matters. In this new work, historian Marc Stein demonstrates convincingly that both sides have it wrong. Focusing on six major Supreme Court cases, Stein examines the more liberal rulings on birth control, abortion, interracial marriage, and obscenity in Griswold, Fanny Hill, Loving, Eisenstadt, and Roe alongside a profoundly conservative ruling on homosexuality in Boutilier.